2021
DOI: 10.3390/jcm10132763
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 and the Pandemic on Tinnitus: A Systematic Review

Abstract: This review aimed to systematically review what has been published regarding tinnitus during the coronavirus disease 2019 (COVID-19) pandemic up to March 2021 by performing both narrative and quantitative meta-analyses. Of the 181 records identified, 33 met the inclusion criteria, which generally had a fair risk of overall bias. In the included, 28 studies focused on the impact of the COVID-19 virus on tinnitus and 5 studies focused on the impact of the pandemic on tinnitus. From the studies identifying the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 67 publications
(305 reference statements)
2
37
1
1
Order By: Relevance
“…Jafari, Kolb, and Mohajerani (2021) included two studies with low tinnitus prevalence in their tinnitus meta-analysis that we excluded as "measured a pre-existing symptom" (Elibol 2021: 1%;Lechien et al 2020: 0.3%) and one study not identified by Almufarrij and Munro (2% in Karadaş, € Ozt€ urk, and Sonkaya 2020). Our revised tinnitus prevalence estimate is close to the 8% (CI: 5-13%) reported in the recent tinnitus meta-analysis by Beukes et al (2021). The biggest difference between the two prevalence estimates is for vertigo/ dizziness, although this is perhaps unsurprising given the difference in foci.…”
Section: Discussionsupporting
confidence: 76%
“…Jafari, Kolb, and Mohajerani (2021) included two studies with low tinnitus prevalence in their tinnitus meta-analysis that we excluded as "measured a pre-existing symptom" (Elibol 2021: 1%;Lechien et al 2020: 0.3%) and one study not identified by Almufarrij and Munro (2% in Karadaş, € Ozt€ urk, and Sonkaya 2020). Our revised tinnitus prevalence estimate is close to the 8% (CI: 5-13%) reported in the recent tinnitus meta-analysis by Beukes et al (2021). The biggest difference between the two prevalence estimates is for vertigo/ dizziness, although this is perhaps unsurprising given the difference in foci.…”
Section: Discussionsupporting
confidence: 76%
“…Evidence for the association of audiovestibular symptoms relating to confirmed cases of COVID-19 has been evaluated in several systematic reviews and meta-analyses (6)(7)(8)(9)(10). These meta-analyses report pooled prevalence estimates of between 3.1% [95% confidence interval (CI): 1.0-9.0] to 7.6% (95% CI: 2.5-15) for new hearing loss, and between 4.5% (95% CI: 1.2-15.0) and 14.8% (CI: 6.3-26.1) for new tinnitus following COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Beukes and colleagues conducted a systematic review to understand the influence of the COVID-19 pandemic or SARS-CoV-2 infection on tinnitus ( 11 ). Although this systematic review included 33 studies, many of the research questions remained unanswered.…”
Section: Introductionmentioning
confidence: 99%